Communication and collaboration skills training in Radiation Oncology in Australia and New Zealand: A qualitative study. Issue 5 (18th January 2022) - Levy, David C.; Naehrig, Diana; Sullivan, Lisa; Chin, Yaw S.
Abstract: Purpose: Effective communication and collaboration with patients, carers and between healthcare professionals improves patient management. This study aimed to explore essential communication and collaboration skills training (CCST) for a radiation oncologist (RO) to inform competencies, learning outcomes and enhance curriculum training methods. Materials and Methods: Eight focus group discussions with 10 fellows and 14 trainees of the Faculty of Radiation Oncology, Royal Australian and New Zealand College of Radiologists (FRO RANZCR) were conducted face to face between October 2018 and March 2019. Participants included doctors from culturally and linguistically diverse backgrounds, working in public and private, metropolitan, and rural sectors. Data were recorded, transcribed verbatim, managed in Excel, and coded using a qualitative content analysis framework. The study was approved by South Eastern Sydney Local Health District HREC (18/186). Participants provided informed written consent. Results: After achieving thematic saturation, four predominant themes emerged. These were as follows: (1) Enablers and barriers to effective communication and collaboration; (2) written communication; (3) communicating bad news; and (4) multidisciplinary team meeting collaboration. Managing uncertainty and workplace culture emerged as interconnected sub‐themes. Conclusions: There is a current lack of CCST in radiation oncology in Australia and New Zealand. The most common theme that emerged to improve CCST focused on increasing the exposure to a variety of communication and collaboration clinical scenarios, which are observed and upon which immediate structured feedback is given. Consultants and trainees offered tangible suggestions on how to improve the curriculum. These findings underscore the importance of using a combination of structured teaching methods and work‐based assessments. CCST templates are recommended.